1997
DOI: 10.1007/bf02785991
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization and kinetic parameter determination of a milk-clotting protease fromMucor bacilliformis

Abstract: Further characterization of an aspartyl protease from Mucor bacilliformis with milk-clotting activity was performed. An extinction coefficient, epsilon 278 cm = 1.61 mL/mg/cm, a molecular mass of 35,400 Da and a pI of 5.2 were determined. Proteolytic activity and kinetic parameters were evaluated by using the hexapeptide Leu-Ser-pNO2-Phe-Nle-Ala-Leu-OMe as the substrate. The effect of pH and temperature on peptide cleavage, as well as protease heat stability, was determined. Such properties, taken as a whole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…7). Similar results have been reported for milk-clotting enzyme from Mucor miehe [44] and Mucor baciliformis [45]. Lin et al [41] also found the same result on a milkclotting agent from lao-chao with Rhizopus oryzae.…”
Section: Ph Optima and Ph Stabilitysupporting
confidence: 89%
“…7). Similar results have been reported for milk-clotting enzyme from Mucor miehe [44] and Mucor baciliformis [45]. Lin et al [41] also found the same result on a milkclotting agent from lao-chao with Rhizopus oryzae.…”
Section: Ph Optima and Ph Stabilitysupporting
confidence: 89%
“…5). The result is in accordance with Venera et al (1997), who observed an optimum pH of 5.5 for MCA from Mucor baciliformis. Hashem (2000) also observed that an increase in the pH of the reaction mixture was associated with a gradual loss of MCA, but at pH 7, 86.79% of the enzyme activity of Penicillium oxalicum was lost and it exhibited a maximum activity at pH 4.…”
Section: Effect Of Ph On Milk Clotting Activity and Stabilitysupporting
confidence: 80%
“…Among those bacterial and fungal rennin substitutes, those from Mucor miehei (Seker et al, 1998), Penicillium oxalicum (Hashem, 2000), Myxococcus xanthus (Petit and Guespin, 1992), Bacillus mesentericus (Stoeva and Mesrob, 1977), Nocardiopsis sp. (Cavalcanti et al, 2004), and Mucor baciliformis (Venera et al, 1997) are the most widely known.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the predicted 3D ribbontype computational representation models for M. circinelloides and M. bacilliformis (online homology modeling with Geno3D was used to create structural models). Venera et al (1997) performed a detailed biochemical and kinetic study on the milk-clotting proteinase from M. bacilliformis. An extinction coefficient, ε 278 cm = 1.61 ml mg −1 cm −1 , a molecular mass of 35.4 kDa, and pI of 5.2 were determined for the protein under study.…”
Section: Recovery and Purification Of Mucor Spp Aspartic Proteinasesmentioning
confidence: 99%
“…and (b) rennin-like enzymes produced by Mucor spp. (Fraile et al 1981;Venera et al 1997;Fernandez-Lahore et al 1999;Neelakantan et al 1999;Andrade et al 2002;Machalinski et al 2006), Rhizomucor spp. (Thakur et al 1990;Escobar and Barnett 1993;Silveira et al 2005;De Lima et al 2008), and Endothia parasitica (Sardinas 1968).…”
mentioning
confidence: 99%